2022
DOI: 10.3390/f13020166
|View full text |Cite
|
Sign up to set email alerts
|

How Does Deforestation Affect the Growth of Cypripedium (Orchidaceae) Species? A Simulation Experiment in Northeast China

Abstract: Due to wild habitat destruction, Cypripedium is among the most endangered groups in China. Determining how Cypripedium respond to environmental changes is curial to their conservation. However, less is known about the effect of deforestation on the growth of Cypripedium. In this study, we selected four Cypripedium species in Northeast China, and conducted conservation-based transplantation simulating deforestation to explore the impact of increased light intensity on the growth of Cypripedium. After three year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…While in Phaius flavus (Blume) Lindl. in southeast China, Li et al (2022) found that populations tended to decrease, and this change was attributed to the low germination rate in the wild and the 2). Such stasis as the predominant life history process has also been registered in other neotropical epiphytic orchids (Tremblay and Hutchings, 2002;Crain et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While in Phaius flavus (Blume) Lindl. in southeast China, Li et al (2022) found that populations tended to decrease, and this change was attributed to the low germination rate in the wild and the 2). Such stasis as the predominant life history process has also been registered in other neotropical epiphytic orchids (Tremblay and Hutchings, 2002;Crain et al, 2019).…”
Section: Discussionmentioning
confidence: 99%